Electroclinical Manifestations of Temporal Lobe Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The relationships between etiology, age at onset and electroclinical findings were examined in 77 children with temporal lobe epilepsy (TLE) reported from University of Verona, Verona, and Niguarda Hospital, Milan, Italy.